Unlocking the spell : a tale of the wide-awake princess - Baker, E. D. (Bloomsbury, 2014)
When Gwendolyn's beloved prince is turned into a bear by a dwarf's curse, her sister Annie uses her ability to fend off magic to find the dwarf and figure out a way to reverse the spell.